Investigation of a transiting planet candidate in Trumpler 37: An astro‐physical false positive eclipsing spectroscopic binary star *. Issue 4 (May 2014) - Errmann, R.; Torres, G.; Schmidt, T.O.B.; Seeliger, M.; Howard, A.W.; Maciejewski, G.; Neuhäuser, R.; Meibom, S.; Kellerer, A.; Dimitrov, D.P.; Dincel, B.; Marka, C.; et al.
Abstract We report our investigation of the first transiting planet candidate from the YETI project in the young (∼4 Myr old) open cluster Trumpler 37. The transit‐like signal detected in the lightcurve of F8V star 2M21385603+5711345 repeats every 1.364894 + 0.000015 days, and has a depth of 54.5 + 0.8 mmag in R. Membership in the cluster is supported by its mean radial velocity and location in the color‐magnitude diagram, while the Li diagnostic and proper motion are inconclusive in this regard. Follow‐up photometric monitoring and adaptive optics imaging allow us to rule out many possible blend scenarios, but our radial‐velocity measurements show it to be an eclipsing single‐lined spectroscopic binary with a late‐type (mid‐M) stellar companion, rather than one of planetary nature. The estimated mass of the companion is 0.15–0.44 M⊙. The search for planets around very young stars such as those targeted by the YETI survey remains of critical importance to understand the early stages of planet formation and evolution. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)